Arabia: the cradle of Islam - Zwemer, Samuel Marinus, 1867-1952. (Piscataway, NJ)
437 sayfa, [25] sayfa resim, portre, harita, plan, tıpkıbasım
Keywords: “This book describes the Arabian peninsula on the eve of the First World War“ -- Yayıncı.